2024
DOI: 10.1021/acs.chemrev.3c00573
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of Fluorescent Probes to Detect Cellular Physical Microenvironments

Junbao Ma,
Rui Sun,
Kaifu Xia
et al.

Abstract: The microenvironment is indispensable for functionality of various biomacromolecules, subcellular compartments, living cells, and organisms. In particular, physical properties within the biological microenvironment could exert profound effects on both the cellular physiology and pathology, with parameters including the polarity, viscosity, pH, and other relevant factors. There is a significant demand to directly visualize and quantitatively measure the fluctuation in the cellular microenvironment with spatiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(4 citation statements)
references
References 534 publications
(1,232 reference statements)
0
4
0
Order By: Relevance
“…By diffusing the probe into condensates formed under different conditions, we found that the emission ratio of Di-4-ANEPPS exhibited ratiometric changes of I 535–545 / I 610–630 in V 120 condensates formed with different ionic conditions, with salting-in ions inducing decreases of I 535–545 / I 610–630 and salting-out ions resulting in increases of I 535–545 / I 610–630 (Figure S22). With more probes that report on the physical microenvironment of biomolecules, further studies could explore other physical properties in condensates. Finally, going beyond the condensates examined in this work, our findings bear implications for how membrane-less organelles would exhibit varying microenvironments in the presence of continuously changing cellular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…By diffusing the probe into condensates formed under different conditions, we found that the emission ratio of Di-4-ANEPPS exhibited ratiometric changes of I 535–545 / I 610–630 in V 120 condensates formed with different ionic conditions, with salting-in ions inducing decreases of I 535–545 / I 610–630 and salting-out ions resulting in increases of I 535–545 / I 610–630 (Figure S22). With more probes that report on the physical microenvironment of biomolecules, further studies could explore other physical properties in condensates. Finally, going beyond the condensates examined in this work, our findings bear implications for how membrane-less organelles would exhibit varying microenvironments in the presence of continuously changing cellular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent and colorimetric probe-based sensing and imaging technology plays an indispensable role in contemporary research domains, leveraging its unmatched sensitivity, specificity, and exceptional spatial and temporal resolution to unlock vast potential in life sciences research and a broad spectrum of analytical applications [ 1 , 2 , 3 , 4 , 5 , 6 ]. These probes are capable of transforming specific molecular or ionic changes, physical states, or environmental variations into quantifiable fluorescent or absorption signals.…”
Section: Introductionmentioning
confidence: 99%
“…[4] As an innate property, fluorescence lifetime is independent of the concentration and intensity of excitation radiation, thus providing a stable signal for imaging applications. On the other hand, the microenvironment could significantly affect fluorescence lifetime, making it a suitable method to quantitatively measure physical microenvironments [5] as represented by polarity, [6] viscosity, [7] temperature, [8] and others. [9] Moreover, fluorescence lifetime multiplexing imaging has emerged as a promising technology that adds additional imaging channels at the same emission wavelength by using probes that can be separated in fluorescence lifetimes.…”
Section: Introductionmentioning
confidence: 99%